Ukraine as a food and grain hub: Impact of science and technology development on food security in the world - Bazhal, Maksym; Koutchma, Tatiana (Frontiers in Food Science and Technology, 2022)
The challenges facing the world today caused by a growing population, reduced resources, global warming, climate shocks, and social and political crises are heavily affecting agri-food systems and supply chains. A global food crisis fueled by conflicts, global warming, climate shocks, and the COVID-19 pandemic is growing because of the bad effects of the war in Ukraine which is one of the world’s major breadbaskets. Science and innovation are the key accelerators to achievingthe complex rapid change in food production, distribution, and consumption required to support the global food security. This article reviews the information on grains, crops, and food production in Ukraine and discusses how the development of food education, science, and technology in Ukraine may impact food security in the world. Ukrainian food science as a part of the global scientific community offers solutions to enhance the stability of the grain and food supply while aiding to reduce food and grain loss, improve food safety, develop novel processing technologies such as pulsed electric field technology (PEF), biotechnology, and extraction methods for biomass recovery or separation technologies, increase environmental safety, energy saving, management of food production and distribution, make advancement in the production of sugar and alcohol, and improvements of food attributes. In support of this conclusion, the main research and development achievements of Ukrainian food scientists are represented.